In vitro behavior of the dentin and enamel calcium hydroxyapatite in human premolars subjected to high temperatures (2016)
This paper details a cross-sectional, descriptive observational in vitro study of a pseudo-experimental nature that analyzes Electron Microscopy (SEM) by scanning the physical behavior of enamel and dentin calcium hydroxyapatite. The purpose is to describe the separation of these two mineralized dental tissues at the dentin-enamel junction (DEJ) when the teeth are subjected to high temperatures. This study provides scientific evidence that may broaden the discussion on the use of separation of the dentin-enamel junction as a constant and repetitive reliable marker for forensic use (use in forensic sciences) that can contribute to the dental identification process and documentation in a legal medical autopsy, given a situation in which bodies or human remains have been burned, carbonizated or incinerated.